Review model dan parameter interaksi pada korelasi kesetimbangan uap-cair dan cair-cair sistem etanol (1) + air (2) + ionic liquids (3) dalam pemurnian bioetanol - Dhoni Hartanto; Bayu Triwibowo (Jurnal Rekayasa Proses, 2014)
Bioethanol is a promising renewable energy resource which can substitute non-renewable energy such as fossil-fuel. Ethanol and water produce azeotropic point in atmospheric pressure condition which can not be separated by ordinary distillation. New class of eco-friendly compounds to be used as entrainer are known as ionic liquids. These ionic liquids are used experimentally in extractive distillation and liquid-liquid extraction. Many researches have been conducted in ethanol (1) + water (2) + ionic liquids (3) systems including vapor-liquid equilibrium (VLE) and liquid-liquid equilibrium (LLE). These researches also produce binary interaction paramaters obtained from equilibrium data correlation using Nonrandom two-liquid (NRTL), Electrolyte-nonrandom two-liquid (e-NRTL), Universal quasi-chemical (UNIQUAC), and Antoine equation. UNIQUAC Functional-group activity coefficients (UNIFAQ) was also used to predict the equilibrium data. Models and binary interaction parameters were used for design, optimization, and control of extractive distillation column and liquid-liquid extraction in bioethanol purification. This paper provides a critical review of models and binary interaction parameters for 43 ethanol (1) + water (2) + ionic liquids (3) systems to obtain appropriate models and binary interaction parameters. Generally, NRTL is the most frequent used model, it is used in 40 systems. NRTL provides satisfactory results in vapor-liquid equilibrium and liquid-liquid equilibrium data correlation due to its characteristics which can correlate well in low pressure polar system. It is shown by small number of root mean square deviation (RMSD) for ∆y and ∆T and average relative deviation (ARD). It can also fit equilibrium data behavior with a good agreement.